'Artefactual anchoring' of strategic spatial planning as persuasive storytelling. (August 2020) - Mäntysalo, Raine; Olesen, Kristian; Granqvist, Kaisa
This article examines the coordinative capacity of strategic spatial planning conducted as persuasive storytelling. It suggests that spatial imaginaries and metaphors developed in storytelling gain coordinative capacity when they perform as boundary objects. Boundary objects are conceptually flexible to lend themselves to the stakeholders' varying interpretations, and artefactually robust to provide joint targets and tools for coordinated strategic action. This is demonstrated with the example of Aalborg, Denmark, where the spatial imaginary of the 'growth axis' and the associated boundary object of the light rail transit/bus rapid transit spine have played important communicative and coordinative roles in the city's spatial strategy of transitioning from an industrial city to a knowledge and culture city. The aim of the Aalborg example is to illustrate the feasibility and relevance of the theoretical approach, developed in the article, for future case research.